Can Food Waste Reduction in Europe Help to Increase Food Availability and Reduce Pressure on Natural Resources Globally? - Yaghoob Jafari; Wolfgang Britz; Hasan Dudu; Roberto Roson; Martina Sartori (German Journal of Agricultural Economics (GJAE), 2020)
In recent years, reducing food waste and loss has become a policy priority in the European Union, but little is known about impacts of related measures in the EU and beyond. This study informs the debate on food waste reduction through a quantitative analysis. It considers adjustment costs for reducing food waste in food processing industries and impacts on food availability, pressure on land and water and other environmental consequences. The results suggest that the leakage effects of global trade may offset almost all benefits of food waste reduction in the EU. We thus conclude that costly efforts to reduce food waste in the EU cannot be motivated by larger contributions to global food availability and environmental benefits. This highlights the need for global coordination of such policies and/or more targeted actions in the EU which focus on specific production chains, where losses can be reduced and environmental gains obtained at a relatively low cost.
Keywords: 330